2017
DOI: 10.21462/jeltl.v2i1.35
|View full text |Cite
|
Sign up to set email alerts
|

Context in English Language Teaching Program: Differentiating between Iranian Public Schools and Private Institutes

Abstract: For some years, there was a debate about the effectiveness of public and private sectors in language learning field, not only in Iran but also in USA and Europe. Actually, a context in which language learners are provided with friendly communicative environment is a great help to learn how to use the language communicatively in authentic situations. Therefore, a context in which the efficient factors are employed more appropriately enables EFL learners to emphasize the communicative use of language in everyday… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…In essence, the revision in the English curriculum and textbooks aimed mainly at inserting the "Islamic-Iranian identity, national culture and local beliefs" (Mirhosseini and Khodakarami, 2015, p. 25), and in practice, public schools' English courses still focused on reading comprehension, grammar, and vocabulary development (Sadeghi and Richards, 2016). Writing practice is limited to composing decontextualized sentences, listening cannot be seen anywhere in the syllabus, and speaking does not move beyond a few drills and short dialogues (Rahimi, 2009;Sadeghi and Richards, 2016;Khoshsima and Hashemi Toroujeni, 2017).…”
Section: Teaching Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…In essence, the revision in the English curriculum and textbooks aimed mainly at inserting the "Islamic-Iranian identity, national culture and local beliefs" (Mirhosseini and Khodakarami, 2015, p. 25), and in practice, public schools' English courses still focused on reading comprehension, grammar, and vocabulary development (Sadeghi and Richards, 2016). Writing practice is limited to composing decontextualized sentences, listening cannot be seen anywhere in the syllabus, and speaking does not move beyond a few drills and short dialogues (Rahimi, 2009;Sadeghi and Richards, 2016;Khoshsima and Hashemi Toroujeni, 2017).…”
Section: Teaching Methodologymentioning
confidence: 99%
“…The EFL teachers play an influential role in students' WTC in many ways, including topic selection (Zarrinabadi, 2014), teaching style (Zarei et al, 2019), and appropriate activities selection (MacIntyre et al, 1998). Public school EFL teachers are forced/accustomed to avoiding employing L2 tasks, which can encourage and facilitate communication in the target language (Khoshsima and Hashemi Toroujeni, 2017;Hosseini Goodrich, 2020). This can be due to the centralized curriculum, the limited classroom time, excessive workload, inappropriate coursebooks, and crowded classes.…”
Section: Teachers' Role and Test-oriented Classroomsmentioning
confidence: 99%
“…From a curriculum perspective, the ministry of education in Iran has published certain books and assigned the same syllabus for public schools across the country. Khoshsima and Hashemi Toroujeni ( 2017 ) revealed that the Iranian public educational system primarily uses Grammar Translation Method (GTM) as its teaching methodology. For many decades, the methodology of such schools consisted of “reading, translation, memorization, and grammar” (Hosseini Goodrich, 2020 , p. 9).…”
Section: Literature Reviewmentioning
confidence: 99%
“…It was a homogeneous group of Mexican teachers who have a BA in English, one of whom was male and three of whom were female. They provided value data concerning the internal realities of the teaching context, which helped gain understanding of how within the setting the issues surrounding the role of ELT (Khoshsima and Hashemi Toroujeni, 2017).…”
Section: Research Context and Participantsmentioning
confidence: 99%